A CASE STUDY ON INTERCULTURAL PROCESS IN LIMITED SETTING - Trihastutie, Nopita (Faculty of Letters, Dr. Soetomo University, 2017)
In a global world, living in other country is no longer unusual thing. Thus, the encounter with other culture is unavoidable. Progressing from ethnocentrism to ethno-relativism is vital for the success of someone living out of his/her mother country. This progress occurs through an intercultural process. A study on the intercultural process utilizes short self-reports and surveys to conduct the assessments of individuals’ attitude, personalities, and values. Conducted in an informal school with a boarding system, this study examines how the intercultural process of foreign teachers and whether this process gives influence to the local students’ cross cultural understanding. An informal school with a boarding system is a limited setting for an intercultural process. However, the interaction is still considered natural for two reasons: firstly, no certain particular cultural obligation for personal and social conduct there; secondly, cultural “take and give” occurs. The process occurs to both foreign teachers and local students. To some extent, the intercultural process of one party contributes the other party’s cross cultural understanding.Key Words: Intercultural Process, Cross Cultural Understanding